Reduced accumulation of isometamidum by drug resistant Trypanosoma congolense - Sutherland, I.A.; Peregrine, A.S.; Lonsdale-Eccles, John D.; Holmes, P.H. (Cambridge University Press, 1991)
The accumulation of the trypanocide isometamidium chloride (Samorin®, RMB Animal Health Ltd, UK) by a range of clones of Trypanosoma congolense with varying sensitivity to the drug, was measured by methods based on the fluorescence of isometamidium. Fluorescence microscopy and flow cytometry showed a reduction in drug accumulation by resistant clones. Fluorescence spectrophotometry demonstrated an inverse correlation between the intensity of cell-associated fluorescence and the level of resistance of the clones expressed in vivo. The addition of the metabolic inhibitor SHAM/glycerol to the incubation medium resulted in a reduction of this apparent difference in drug accumulation between the clones; those clones which were sensitive to isometamidium showed a reduction in fluorescence while a percentage increase in fluorescence was observed as clones became more resistant to the trypanocide. These observations may be of value for the in vitro detection of resistant T. congolense populations and may also be used to estimate the mean level of resistance in a given sample. The results also imply that decreased accumulation of isometamidium by drug-resistant clones of the parasite may be responsible for the reduction in sensitivity.